Enacting Data Protection Law in Nepal - Chaudhary, Newal (Prashasan: The Nepalese Journal of Public Administration, 2025)
In today's interconnected world, digital transactions and online activities have become indispensable facets of daily life, revolutionizing the way we communicate, conduct business, and access information. However, this rapid digitalization has also raised a critical concern, the protection of personal and sensitive data. As individuals and organizations increasingly rely on digital platforms and services, the risk of unauthorized access, disclosure, or theft of confidential information has escalated significantly. Data breaches, which involve the unauthorized acquisition of sensitive data, pose grave risks to both individuals and organizations. For individuals, a data breach can lead to identity theft, financial fraud, and misuse of personal information, potentially causing long-lasting harm and financial losses. Organizations, on the other hand, may face severe reputational damage, loss of customer trust, legal liabilities, and substantial financial consequences resulting from data breaches. Nepal, like many other nations, has witnessed a surge in data breach incidents in recent years, exposing vulnerabilities in its digital landscape and highlighting the pressing need for a comprehensive legal framework to address this critical issue. High-profile cases, such as the breach of the Ramailo app database in 2023 and the Vianet data breach in 2020, have underscored the urgency of implementing robust measures to safeguard the privacy and security of individuals' personal information. This article explores the current legislative landscape in Nepal by examining existing laws and policies related to cybersecurity and data protection. It critically evaluates the gaps and shortcomings in the current legal framework, highlighting the lack of specific provisions and enforcement mechanisms needed to effectively address the complexities of data breaches. Through comprehensive analysis, the article advocates for the enactment of a dedicated data protection law in Nepal. Such a law would encompass key aspects like mandatory breach notification requirements, stringent data protection standards, and effective enforcement mechanisms. By addressing these crucial elements, a robust data protection law can safeguard the rights and interests of Nepali citizens, fostering a secure and trusted digital environment that promotes economic growth, innovation, and public confidence in the digital ecosystem. This article emphasizes the importance of a comprehensive legal framework that aligns with international best practices and facilitates cross-border cooperation in combating the global threat of data breaches. By establishing clear guidelines, accountability measures, and consumer protections, a dedicated data protection law can empower individuals, organizations, and regulatory bodies to proactively address data breaches, mitigate potential risks, and uphold the principles of privacy and data security in the digital age.